How Not to Write A Medical Paper - Heinemann, Markus K. (Thieme, 2016)
Writing a medical paper, or any other scientific text, is full of pitfalls which make it difficult to get it accepted for publication. This unique book gives practical advice on how one can circumvent these dangers. It is richly filled with examples, predominantly negative ones. which exhibit how one should not write a medical paper. This book highlights the fallibilities that manuscripts are often susceptible to, and hence will help writers avoid committing those mistakes. Special Features: Abundant information about a complex subject condensed in a small format Numerous examples from bad man.